Mutations of von Willebrand factor gene in families with von Willebrand disease in the Aland Islands. - Zhang, Z P (1993)
Patients with von Willebrand disease in four families in the Aland Islands, including the original family that was described in 1926 by the Finnish physician von Willebrand, were screened for mutations in the Swedish "hot-spot" regions (exons 18, 28, 32, 43, and 45) of the von Willebrand factor gene. One cytosine deletion in exon 18 was detected in each of these families. Linkage analysis and genealogical studies suggest that the deletion present in these four families probably has an origin in common with the mutations in the Swedish patients. Apart from the deletion in exon 18, two close transitions (G-->A at S1263 and C-->T at P1266) in exon 28 on the same chromosome were identified in one individual who married into the original family and in his two children. The transitions could be due to a recombination between the von Willebrand factor gene and its pseudogene.